Traditional Preaching Patterns In The Cireundeu Traditional Village - Ahmad Aliadin; Iwan Sopwandin; Anwar Shadikin (STAI AL-FALAH CICALENGKA, 2021)
The success of a missionary in delivering da'wah cannot be separated from the effective pattern he uses. Tabligh or Da'wah is a moral force that is able to drive social change and offers an alternative in building the future dynamics of the ummah, by taking the right, creative and wise ways and strategies. This paper aims to describe the pattern of da'wah in the Cireundeu Cimahi Traditional Village. This research uses descriptive analysis method with a qualitative approach. Data collection techniques used are observation, interviews, and documentation studies. The results of this study explain that Ustad Abdullah uses a traditionalist pattern, namely conveying Islamic messages or teachings from the yellow book. Using the method of delivery by word of mouth, by action, and equipped with writings from books, magazines or relevant leaflets obtained from outside. Cultural communication used is low context communication. His da'wah pattern had a very significant impact on the development of Islam in the Cireundeu Traditional Village. The public's interest in exploring and practicing Islamic teachings is also very enthusiastic. Keywords: Da'wah Pattern, Traditionalist, Cireundeu, Indonesia Abstrak Keberhasilan seorang mubaligh dalam menyampaikan dakwah tidak terlepas dari pola efetif yang digunakannya. Tabligh atau Dakwah merupakan kekuatan moral yang mampu menggerakan perubahan sosial serta menawarkan satu alternatif dalam membangun dinamika masa depan umat, dengan menempuh cara dan strategi yang benar, keratif dan bijak. Tulisan ini bertujuan untuk memaparkan pola dakwah di Kampung Adat Cireundeu Cimahi. Penelitian ini menggunakan metode analisis deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data yang digunakan yaitu observasi, wawancara, dan studi dokumentasi. Hasil penelitian ini menjelaskan bahwa Ustad Abdullah menggunakan pola tradisionalis, yaitu menyampaikan pesan-pesan atau ajaran Islam yang berasal dari kitab kuning. Menggunakan metode penyampaian Bil Lisan, Bil Hal, dan dilengkapi dengan tulisan dari buku, majalah atau selembaran relevan yang didapatkan dari luar. Komunikasi budaya yang digunakan yaitu komunikasi konteks rendah. Pola dakwahnya memberikan dampak yang sangat signifikan terhadap perkembangan Islam di Kampung Adat Cireundeu. Minat masyarakat untuk mendalami dan mengamalkan ajaran Islam juga sangat antusias. Kata Kunci: Pola Dakwah, Tradisionalis, Cireundeu, Indonesia